GENDER IMBALANCE IN PHYSICS: THE ROLE OF SOCIALIZATION - Ogumogu, Augustine Excellent (Sokoto Educational Review, 2017)
Gender imbalance in terms of enrolment performance and the number of professionals in physics has been an issue of concern for stakeholders in physics education. The purpose of this paper is to advance some sociological reasons why females are underrepresented in physics and what can be done to address this gender imbalance in physics; particularly in the classroom. In this paper it was argued that the gender imbalance in physics is not necessarily due to gender brain-difference model as believed by some researchers but rather it may be due to gender-role socialization through some conscious and unconscious socialization activities in the environment. Recommendations were made on how to bridge this gender imbalance in physics; one of such recommendations include that counselors should encourage female students’ to be actively involved in physics or its related activities instead of running away from the subject.